Section 2C(1) of the Wills Act 7 of 1953 and the Meaning of “Spouse” Moosa No v Minister of Justice 2018 (5) SA 13 (CC) - Wood-Bodley, Michael Cameron (Obiter, 2020)
It happens from time to time that a beneficiary under a will chooses not to accept his or her inheritance. One possible reason, which is relevant to the discussion below, may be the beneficiary’s desire to allow persons to inherit, or inherit more than would otherwise have been the case, as a result of the renunciation. (For a fuller discussion of the various circumstances in which a beneficiary may wish to renounce, see Corbett, Hofmeyr and Kahn The Law of Succession in South Africa 2ed (2001) (Corbett) 17–18.)The effect of a renunciation on the devolution of the deceased testator’s estate is determined by a number of factors, including the particular provisions of the will, and varies from case to case. One determining factor is section 2C of the Wills Act 7 of 1953 (as amended) – of which the counterpart in intestate succession is s 1(6) and (7) of the Intestate Succession Act 81 of 1987 (as amended).